RhPDCD5 combined with dexamethasone increases antitumor activity in multiple myeloma partially via inhibiting the Wnt signalling pathway. (9th November 2017) - Cheng, Qian; Liu, Liping; Fu, Yunfeng; Zhang, Yanan; Yang, Ye; Liu, Jing
Summary: Multiple myeloma (MM) is one of the most common hematological malignancies and characterized by the clonal accumulation of malignant plasma cells. Significant progress has been made in MM treatment recently, while MM still remains incurable. Our previous studies showed that the recombined human programmed cell death 5 (rhPDCD5) can promote MM apoptosis induced by dexamethasone (Dex). Here, we expanded the findings by showing that the rhPDCD5 alone could not induce an obvious growth inhibition of U266 cells (a MM cell line). Of note, with the combination of dexamethasone (Dex), the growth of MM cells was significantly inhibited and accompanied with the cell cycle arrest in G0/G1. For mechanism study, we found that the combination treatment of rhPDCD5 plus Dex downregulated the mRNA and protein expressions of Wnt effectors including β‐catenin, β‐catenin (Ser675), TCF4, survivin and c‐Myc when compared to Dex only. Moreover, the activation of WNT pathway induced by LiCl can also be inhibited by this combination treatment. Taken together, our study demonstrated that the combination of rhPDCD5 and Dex can suppress the proliferation of multiple myeloma cells partially via inhibiting the WNT signalling pathway.